A multi‐institutional phase 2 study of neoadjuvant gemcitabine and oxaliplatin with radiation therapy in patients with pancreatic cancer. Issue 15 (29th May 2013) - Kim, Edward J.; Ben‐Josef, Edgar; Herman, Joseph M.; Bekaii‐Saab, Tanios; Dawson, Laura A.; Griffith, Kent A.; Francis, Isaac R.; Greenson, Joel K.; Simeone, Diane M.; Lawrence, Theodore S.; Laheru, Daniel; Wolfgang, Christopher L.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The purpose of this study was to evaluate preoperative treatment with full‐dose gemcitabine, oxaliplatin, and radiation therapy (RT) in patients with localized pancreatic cancer. METHODS Eligibility included confirmation of adenocarcinoma, resectable or borderline resectable disease, a performance status ≤2, and adequate organ function. Treatment consisted of two 28‐day cycles of gemcitabine (1 g/m2 over 30 minutes on days 1, 8, and 15) and oxaliplatin (85 mg/m2 on days 1 and 15) with RT during cycle 1 (30 Gray [Gy] in 2‐Gy fractions). Patients were evaluated for surgery after cycle 2. Patients who underwent resection received 2 cycles of adjuvant chemotherapy. RESULTS Sixty‐eight evaluable patients received treatment at 4 centers. By central radiology review, 23 patients had resectable disease, 39 patients had borderline resectable disease, and 6 patients had unresectable disease. Sixty‐six patients (97%) completed cycle 1 with RT, and 61 patients (90%) completed cycle 2. Grade ≥3 adverse events during preoperative therapy included neutropenia (32%), thrombocytopenia (25%), and biliary obstruction/cholangitis (14%). Forty‐three patients underwent resection (63%), and complete (R0) resection was achieved in 36 of those 43 patients (84%). The median overall survival was 18.2 months (95% confidence interval, 13–26.9 months) for all patients, 27.1 months (95% confidence interval, 21.2–47.1 months) for those who underwent resection, and 10.9 months (95% confidence interval, 6.1–12.6 months) for those who did not undergo resection. A decrease in CA 19‐9 level after neoadjuvant therapy was associated with R0 resection (P = .02), which resulted in a median survival of 34.6 months (95% confidence interval, 20.3–47.1 months). Fourteen patients (21%) are alive and disease free at a median follow‐up of 31.4 months (range, 24–47.6 months). CONCLUSIONS Preoperative therapy with full‐dose gemcitabine, oxaliplatin, and RT was feasible and resulted in a high percentage of R0 resections. The current results are particularly encouraging, because the majority of patients had borderline resectable disease. Cancer 2013;119:2692–2700. © 2013 American Cancer Society.